Impact evaluation of a conditional cash transfer program: the Nicaraguan Red de Protección Social - Maluccio, John; Flores, Rafael (International Food Policy Research Institute, 2005)
In 2000, the Nicaraguan government implemented a conditional cash transfer program designed to improve the nutritional, health, and educational status of poor households, and thereby to reduce short- and long-term poverty. Based on the Mexican government’s successful PROGRESA program, Nicaragua’s Red de Protección Social (RPS) sought to supplement household income, reduce primary school dropout rates, and increase the health care and nutritional status of children under the age of five. This report represents IFPRI’s evaluation of phase I of RPS. It shows that the program was effective in low-income areas and particularly effective when addressing health care and education needs. The report offers the first extensive assessment of a Nicaraguan government antipoverty program.